2023
DOI: 10.3389/fpsyg.2022.1089654
|View full text |Cite
|
Sign up to set email alerts
|

Emotional stimulation processing characteristics in depression: Meta-analysis of eye tracking findings

Abstract: ObjectiveTo systematically evaluate the attentional bias in patients with depression toward emotional stimuli and to explore eye movement indicators and potential regulatory variables that can distinguish such patients from healthy individuals.MethodsCase–control studies regarding eye-tracking in major depressive disorder published in PubMed, Web of Science, ScienceDirect, The Cochrane Library, EBSCOhost, Embase, China National Knowledge Infrastructure, Wanfang, and VIP databases from database initiation until… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…It is a measure commonly used in eye-tracking studies to understand visual attention and cognitive processes. Prior studies have suggested that the duration of the first fixation while visually searching typically indicates the characteristics of early processing [ 28 ]. Similarly, the first fixation primarily indicates the initial attention allocated to processing the directional characteristics of a stimulus [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is a measure commonly used in eye-tracking studies to understand visual attention and cognitive processes. Prior studies have suggested that the duration of the first fixation while visually searching typically indicates the characteristics of early processing [ 28 ]. Similarly, the first fixation primarily indicates the initial attention allocated to processing the directional characteristics of a stimulus [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Klawohn et al (2020) found that the depressed group dwelled longer on sad faces than healthy people. A systematic review by Huang et al (2023) also pointed out the negative attention bias toward emotional stimuli regarding eye-tracking. On the other hand, an increasing amount of studies based on functional magnetic resonance imaging (fMRI) have also revealed disrupted brain function of depression patients in response to emotional faces.…”
Section: Introductionmentioning
confidence: 99%